The Moral Orders of Matchmaking Work: Digitization of Matrimonial Services and the Future of Work - Lalvani, Simiran; Pal, Joyojeet (CSCW 2022, 2022)
The digitization of matrimonial matchmaking has implications for work but also subjective notions of family, femininity, parent-child relations, community boundaries which this work relies on. This paper is based on qualitative, ethnographic fieldwork with matchmakers working with middle-class, upper-caste Hindu and Parsi communities in metropolitan India and offering services alongside, or as an alternative to the now widely used online matrimonial services. Through our fieldwork, we found all matchmakers engaged with digital technologies' involvement in the ongoing churn around modern choice. Matchmakers engaged with this wider social discourse through ideas of trust, autonomy and genealogy and in doing so they responded to and re/produced varying imaginations of the future of families, community, individuals. Our findings contribute to an understanding of the digitization of a service as well as make a case for widening the conceptual scope of the future of work debate currently dominated by economistic conceptions of work. By paying attention to the links between the productive and reproductive spheres of life, we follow labor and capital into the families and communities they reside in order to see the variety of moral projects capital can be invested in.